Pengaruh Peraturan Bank Indonesia No.11/33/PBI/2009 Terhadap Kinerja Keuangan Pada BNI Syariah Cabang Kediri. - Samodra, Afim Triyoga; Cahyono, Hendry (Universitas Negeri Surabaya, 2018)
In improving good corporate governance, it is required by employees who can apply the rules set by Bank Indonesia Regulation through financial performance so that the company can develop well. This research is quantitative research which aim to know how big influence of regulation of Bank Indonesia No.11/33/PBI/2009 to Financial Performance. From the result of research conducted with independent variable The principle of transparency, accountability principle, responsibility principle, professional principle and principle of equality and fairness with ROA, ROE, NPF BOPO, NIM and FDR by purposive sampling technique with questionnaire dispersion method can be concluded that Bank Indonesia Regulation No.11/33/PBI 2009 effect on the performance of employees BNI Syariah Branch Kediri